Gestalt therapy : advances in theory and practice - Bar-Yoseph, Talia Levine (Advancing theory in therapy., 2012)
The Gestalt approach is based on the philosophy that the human being is born with the healthy ability to regulate needs and wants in relationship with the environment in which she/he lives. Heightening of personal awareness and exploration of needs is enabled by the therapist who actively engages in supporting and assisting the therapeutic journey of the client. Gestalt Therapy: Advances in Theory and Practice is a collaboration of some of the best thinkers in the Gestalt therapy approach. It offers a summary of recent advances in theory and practice, and novel ideas for future development. Ea.